2017
DOI: 10.1097/mib.0000000000001178
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status Is Associated with Hepcidin and Hemoglobin Concentrations in Children with Inflammatory Bowel Disease

Abstract: BACKGROUND Anemia, iron deficiency and hypovitaminosis D are well-known comorbidities in inflammatory bowel disease (IBD). Epidemiologic studies have linked vitamin D deficiency with increased risk of anemia, and in vitro studies suggest that vitamin D may improve iron recycling through down-regulatory effects on hepcidin and pro-inflammatory cytokines. DESIGN/METHODS We aimed to investigate the association of vitamin D status with inflammation, iron biomarkers, and anemia in pediatric IBD. Cross-sectional d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 46 publications
5
30
0
1
Order By: Relevance
“…In the present study mean vitamin D3 in the older women group (group II) 11.8 ± 3.5 ng/dL was signi icantly lower than younger women (group I) 35.3 ± 12.2 ng/dL (p-value < 0.001), similar inding observed for ferritin (19.6 ± 13.9 vs. 66.7 ± 52.1, pvalue <0.001), additionally there was signi icant direct correlation between ferritin and vitamin D3 in (SIM et al, 2010) was in agreement with present study in which low vitamin D (<30 ng/dL) associated with elevated Ferritin compared to normal vitamin D (≥30 ng/dL) [364 vs. 189 ng/ml, p-value = 0.01] (SIM et al, 2010;SYED et al, 2017) study, in linear regression models, vitamin D insuf iciency was associated with increased hepcidin levels (β [SE] = 0.6 [0.2], P = 0.01) and reduced hemoglobin (β [SE] = -0.9 [0.5], P = 0.046), suggesting that the concentrations of 25(OH)D ≥30 ng/mL are associated with lower hepcidin and higher hemoglobin levels (SYED et al, 2017) .…”
Section: Resultssupporting
confidence: 91%
“…In the present study mean vitamin D3 in the older women group (group II) 11.8 ± 3.5 ng/dL was signi icantly lower than younger women (group I) 35.3 ± 12.2 ng/dL (p-value < 0.001), similar inding observed for ferritin (19.6 ± 13.9 vs. 66.7 ± 52.1, pvalue <0.001), additionally there was signi icant direct correlation between ferritin and vitamin D3 in (SIM et al, 2010) was in agreement with present study in which low vitamin D (<30 ng/dL) associated with elevated Ferritin compared to normal vitamin D (≥30 ng/dL) [364 vs. 189 ng/ml, p-value = 0.01] (SIM et al, 2010;SYED et al, 2017) study, in linear regression models, vitamin D insuf iciency was associated with increased hepcidin levels (β [SE] = 0.6 [0.2], P = 0.01) and reduced hemoglobin (β [SE] = -0.9 [0.5], P = 0.046), suggesting that the concentrations of 25(OH)D ≥30 ng/mL are associated with lower hepcidin and higher hemoglobin levels (SYED et al, 2017) .…”
Section: Resultssupporting
confidence: 91%
“…An even stronger correlation with PTH has been observed for 24,25OH2D. However, it might be useful as an indicator of tissue-level 1,25OH2D activity [22,27]. While both parameters could be used to gain a better insight into individual vitamin D status, neither 1,25OH2D nor 24,25OH2D seems to be a better sole marker of vitamin D status than 25OHD.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have also demonstrated poor vitamin D status to be an independent risk factor for the incidence of colorectal cancer in individuals with IBD [21]. Observational data confirmed low levels of vitamin D to be associated with increased concentrations of hepcidin and thus with anemia, one of the most prevalent extraintestinal complications of IBD [22]. Additionally, vitamin D insufficiency/deficiency has been shown to be associated with poor health-related quality of life (HRQOL) outcomes [23].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a study in children has shown that supplementation of vitamin D facilitates increased haemoglobin levels. Here plasma concentrations of 25-hydroxyvitamin D (25(OH)D) below 30 ng/mL (i.e., vitamin D deficiency) were associated with increased hepcidin concentrations and reduced haemoglobin concentrations compared with individuals with plasma 25(OH)D concentrations above 30 ng/mL [ 100 ]. Because vitamin D deficiency is frequent in IBD [ 101 ] and because vitamin D has been shown to inhibit hepcidin expression [ 102 ] and to possess important immunologic effects of benefit in the clinical course of patients with IBD [ 103 , 104 , 105 ], normalization of vitamin D is important for elevating the haemoglobin level in these patients.…”
Section: Iron Replacement Formulationsmentioning
confidence: 99%